Longitudinal therapy monitoring of ALK-positive lung cancer by combined copy number and targeted mutation profiling of cell-free DNA - Dietz, Steffen; Christopoulos, Petros; Yuan, Zhao; Angeles, Arlou Kristina J.; Gu, Lisa; Volckmar, Anna-Lena; Ogrodnik, Simon; Janke, Florian; Dalle Fratte, Chiara; Zemojtel, Tomasz; Schneider, Marc; Kazdal, Daniel; et al. (EBioMedicine, 2020)
Background - Targeted therapies (TKI) have improved the prognosis of ALK-rearranged lung cancer (ALK+ NSCLC), but clinical courses vary widely. Early identification and molecular characterisation of treatment failure have key importance for subsequent therapies. We performed copy number variation (CNV) profiling and targeted panel sequencing from cell-free DNA (cfDNA) to monitor ALK+ NSCLC. - Methods - 271 longitudinal plasma DNA samples from 73 patients with TKI-treated metastatic ALK+ NSCLC were analysed by capture-based targeted (average coverage 4,100x), and shallow whole genome sequencing (sWGS, 0.5x). Mutations were called using standard algorithms. CNVs were quantified using the trimmed median absolute deviation from copy number neutrality (t-MAD). - Findings - cfDNA mutations were identified in 58% of patients. They included several potentially actionable alterations, e.g. in the genes BRAF, ERBB2, and KIT. sWGS detected CNVs in 18% of samples, compared to 6% using targeted sequencing. Several of the CNVs included potentially druggable targets, such as regions harboring EGFR, ERBB2, and MET. Circulating tumour DNA (ctDNA) mutations and t-MAD scores increased during treatment, correlated with markers of higher molecular risk, such as the EML4-ALK variant 3 and/or TP53 mutations, and were associated with shorter patient survival. Importantly, t-MAD scores reflected the tumour remission status in serial samples similar to mutant ctDNA allele frequencies, and increased with disease progression in 79% (34/43) of cases, including those without detectable single nucleotide variant (SNV). - Interpretation - Combined copy number and targeted mutation profiling could improve monitoring of ALK+ NSCLC. Potential advantages include the identification of treatment failure, in particular for patients without detectable mutations, and broader detection of genomic changes acquired during therapy, especially in later treatment lines and in high-risk patients. - Funding - This work was supported by the German Center for Lung Research (DZL), by the German Cancer Consortium (DKTK), by the Heidelberg Center for Personalized Oncology at the German Cancer Research Center (DKFZ-HIPO), and by Roche Sequencing Solutions (Pleasanton, CA, USA).